Eyewitness to the assassination of Archduke Francis Ferdinand - O'Keefe, Emily (Eyewitness to World War I., 2018)
Briefly examines the events surrounding the assassination of Archduke Francis Ferdinand and how they led to World War I. Includes a glossary, review questions, and index.